2017
DOI: 10.1063/1.4982938
|View full text |Cite
|
Sign up to set email alerts
|

Shear flow behaviors of rod-coil diblock copolymers in solution: A nonequilibrium dissipative particle dynamics simulation

Abstract: We employed the nonequilibrium dissipative particle dynamics method to study the shear flow behaviors of rod-coil diblock copolymers in solutions. The effects of copolymer concentrations and molecular architecture on the rheology are investigated. The simulated results show that the shear flow behaviors change from Newtonian to non-Newtonian when the morphologies transform from micelles to gels by increasing the copolymer concentrations. For the non-Newtonian systems, it was found that the curve of the viscosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Nonequilibrium simulation based on the standard MD method is employed to simulate the polymeric systems subjected to an oscillatory shear field. Lees-Edwards “sliding brick” boundary conditions were the most widely adopted to introduce a shear field. , Alternatively, we employ a “box deforming” technique which is conceptually identical to the Lees-Edwards boundary conditions. , In the simulations, SLLOD algorithm coupled with the “box deforming” technique is adopted to introduce a shear field in x -direction and velocity gradient in y -direction where e x is the unit vector along x -direction. r i , v i , and f i are the position, velocity, and force of i th bead, respectively.…”
Section: Methods and Modelmentioning
confidence: 99%
“…Nonequilibrium simulation based on the standard MD method is employed to simulate the polymeric systems subjected to an oscillatory shear field. Lees-Edwards “sliding brick” boundary conditions were the most widely adopted to introduce a shear field. , Alternatively, we employ a “box deforming” technique which is conceptually identical to the Lees-Edwards boundary conditions. , In the simulations, SLLOD algorithm coupled with the “box deforming” technique is adopted to introduce a shear field in x -direction and velocity gradient in y -direction where e x is the unit vector along x -direction. r i , v i , and f i are the position, velocity, and force of i th bead, respectively.…”
Section: Methods and Modelmentioning
confidence: 99%
“…Xu at el. [24] studied the shear flow of rod-coil diblock copolymers in solutions by employing the nonequilibrium dissipative particle dynamics method. Kong et al [25] studied the rheological properties of surfactant solutions by using dissipative particle dynamics algorithm too.…”
Section: Introduction mentioning
confidence: 99%
“…Theory and simulation are of particular use to develop a fundamental understanding of the structure–property relationship of the hierarchical structures. On the aspect of structure studies, self-consistent field (SCFT) theory and dissipative particle dynamics (DPD) simulation have successfully been used to predict the structures and morphologies constituted by the multiblock copolymers. Lin and coauthors have used SCFT and DPD to reproduce a series of hierarchical structures found in the experiments. , On the aspect of property studies, nonequilibrium molecular dynamics (NEMD) simulations are widely utilized to examine the rheological properties of block copolymers. Ganesan et al combined nonequilibrium oscillatory shear technique and DPD simulation to study the viscoelastic properties of ABA triblock copolymers, which can form a gel in solution due to the amphiphilic interactions . They demonstrated that their simulation results show a high coincidence with other theoretical calculations and experimental findings.…”
Section: Introductionmentioning
confidence: 99%